1977
DOI: 10.1159/000260244
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Fluoride Uptake in Human Dental Enamel from Various Fluoride Solutions

Abstract: The fluoride uptake from six different fluoride solutions applied to the buccal surfaces of extracted, newly erupted premolars was measured. The fluoride concentration of two symmetrically situated areas were compared at various distances from the enamel surface after treatment of one of the areas with a fluoride solution. Exposure of enamel to sodium fluoride, acidic phosphate fluoride, monofluorophosphate, stannous fluoride, sodium hexafluorostannate and cetylaminhydrofluoride was found to produce significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
0
1

Year Published

1979
1979
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 12 publications
4
11
0
1
Order By: Relevance
“…The mean fluoride concentrations of the buccal enamel at 5 and 10 urn (966.8 and 695.5 ppm, re spectively) were similar to the results reported by Kirkegaard [1977] (892.5 and 670.7 for extracted pre molars at 6 and 10 urn) and to the result of Pearce et al [1982] who reported 995 ppm in the outermost 5 urn of newly erupted premolars.…”
Section: Pre-treatment Fluoride Concentrationssupporting
confidence: 88%
See 2 more Smart Citations
“…The mean fluoride concentrations of the buccal enamel at 5 and 10 urn (966.8 and 695.5 ppm, re spectively) were similar to the results reported by Kirkegaard [1977] (892.5 and 670.7 for extracted pre molars at 6 and 10 urn) and to the result of Pearce et al [1982] who reported 995 ppm in the outermost 5 urn of newly erupted premolars.…”
Section: Pre-treatment Fluoride Concentrationssupporting
confidence: 88%
“…Despite the great variety of experimental design and technique, previous reports [Antila et al, 1972;Kirkegaard, 1977;Barbakow et al, 1983] have indi cated higher uptake from amine fluoride agents com pared with other test agents such as neutral sodium fluoride, acid phosphate fluoride, hexafluorostannate, monofluorophosphate, and stannous fluo ride. Only Arends and Schuthof [1975] reported that the fluoride content after amine fluoride application was lower than that after similar treatment with other fluoride preparations (APF, NH4F and a urethane lacquer-containing silane fluoride).…”
Section: Pre-treatment Fluoride Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may well be that concentrations lower than 0.4% may be equally effective. In vitro studies on sound human enamel have recently shown that there was no statistically signif icant difference between the amount of fluoride ingested after the application of APF gels that varied in fluoride concentra tion between 0.1 and 1.23% [Dijkman et al, 1982], Kirkegaard[ 1977] compared the fluoride uptake in sound human enamel after the application of NaF, APF, MFP, SnF2, Na2SnF6 and amine fluoride, BaijotStroobants and Vreven [1979] compared APF, MFP and amine fluoride. Both groups of workers found that the highest enamel fluoride levels were found after the application of amine fluoride solutions.…”
mentioning
confidence: 99%
“…Comparative studies of fluoride uptake at the enamel surface from various fluoridecontaining gels and solutions have been pre viously reported [Muhlemann et al, 1967;Arends and Schuthof, 1975;Kirkegaard, 1977],…”
mentioning
confidence: 99%